2020
DOI: 10.21203/rs.3.rs-99747/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroprotective Effects of Intraoperative Dexmedetomidine Infusion Combined With Goal-directed Hemodynamic Therapy for Patients Undergoing Cranial Surgery: A Double-blinded Randomized Controlled Trial

Abstract: BackgroundDespite dexmedetomidine may be neuroprotective in patients undergoing cranial surgery by inhibiting neuroinflammation; however, it reduces cardiac output and cerebral blood flow. We proposed that dexmedetomidine infusion combined with goal-directed hemodynamic therapy (GDHT) could improve cranial surgery neurological outcomes without hemodynamic perturbation.MethodsA randomized, double-blind trial was conducted. One hundred sixty adult patients undergoing elective cranial surgery received either dexm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…We read with great interest the article of Chen et al 1 that evaluated the neuroprotective effect of intra-operative dexmedetomidine (DEX) infusion combined with goal-directed haemodynamic therapy (GDHT) in patients undergoing cranial surgery. The author concluded that DEX combined with GDHT could attenuate postoperative disability and prevention of delirium through mitigation of neuro-inflammation during cranial surgery.…”
mentioning
confidence: 99%
“…We read with great interest the article of Chen et al 1 that evaluated the neuroprotective effect of intra-operative dexmedetomidine (DEX) infusion combined with goal-directed haemodynamic therapy (GDHT) in patients undergoing cranial surgery. The author concluded that DEX combined with GDHT could attenuate postoperative disability and prevention of delirium through mitigation of neuro-inflammation during cranial surgery.…”
mentioning
confidence: 99%